A influencia da torcida sobre desempenho do jogo de esquipes de futsal de escolares do ensino médio - (:unkn) unknown (FEFF - Faculdade de Educação Física e Fisioterapia, 2025)
This Final Paper aims to investigate whether the presence of the crowd influences the performance of the men's futsal teams during the interclass competition in a public high school in the city of Manaus. The study explores the effects of cheering for and against, in addition to identifying the factors that most interfere with athletes' performance. Futsal, as a relevant school activity, involves not only physical aspects, but also psychological aspects, with the presence of the crowd being an external factor that can affect the performance of the players. The theory of self-efficacy (BANDURA 1997) serves as a basis for investigating how the support of the crowd can impact the confidence and motivation of athletes, enhancing or impairing their performance. The research was conducted with 40 male athletes, aged between 14 and 18 years, participating in an interclass competition. Data collection was carried out through questionnaires, with questions focused on the players' perceptions of the effects of the crowd on their performances. Data analysis was done by categorizing objective responses, looking for patterns in the influences of both positive and negative fans. The literature review points out that the presence of fans can affect the motivation and self-efficacy of players, with both beneficial and harmful impacts depending on the individual interpretation of each athlete. The expected results are to provide a detailed analysis of how external factors, such as crowding, can modify the competitive and emotional context of athletes in the school environment, and how this reflects on their performance in futsal games. The research also seeks to contribute to the understanding of the impact of extrinsic motivation on sports performance, especially in school competitions in Brazil.
Keywords: Motivação; Autoeficácia; Influencia torcida; Desempenho coletivo; Competição escolar; CIENCIAS DA SAUDE: EDUCAÇÃO FÍSICA; .; .